Quantitative Evaluation and Visualization of Lumbar Foraminal Nerve Root Entrapment by Using Diffusion Tensor Imaging: Preliminary Results - Eguchi, Y.; Ohtori, S.; Orita, S.; Kamoda, H.; Arai, G.; Ishikawa, T.; Miyagi, M.; Inoue, G.; Suzuki, M.; Masuda, Y.; Andou, H.; Takaso, M.; et al. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: DTI can provide valuable structural information that may become an innovative tool in evaluating lumbar foraminal nerve root entrapment. The purpose of this study was to visualize the lumbar nerve roots and to measure their FA in healthy volunteers and patients with lumbar foraminal stenosis by using DTI and tractography with 3T MR imaging. MATERIALS AND METHODS: Eight patients with lumbar foraminal stenosis and 8 healthy volunteers underwent 3T MR imaging. In all subjects, DTI was performed with echo-planar imaging at a b-value of 800 s/mm2 and the lumbar nerve roots were visualized with tractography. Mean FA values in the lumbar nerve roots were quantified on DTI images. RESULTS: In all subjects, the lumbar nerve roots were clearly visualized with tractography. In all patients, tractography also showed abnormalities such as tract disruption, nerve narrowing, and indentation in their course through the foramen. Mean FA values were significantly lower in entrapped roots than in intact roots. CONCLUSIONS: We demonstrated that DTI and tractography of human lumbar nerves can visualize and quantitatively evaluate lumbar nerve entrapment with foraminal stenosis. We believe that DWI is a potential tool for the diagnosis of lumbar nerve entrapment. FAfractional anisotropyMPGmotion probing gradientVASvisual analog scale